Tie-1：A Potential Target for Anti-Angiogenesis Therapy - 杨萍 陈娜 贾静辉 高雪娇 李诗函 蔡晶 王泽华 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
The tyrosine kinase system angiopoietin（Ang）/Tie interacts with vascular endothelial growth factor pathway and regulates vessel quiescence in adults as well as later steps of the angiogenic cascade related to vessel maturation. Since all Angs are able to bind to Tie-2 but none binds to Tie-1,the function of Tie-2 and its ligands have captured attention. However,emerging evidence indicates unique roles of the orphan receptor Tie-1 in angiogenesis under physiological and pathological conditions. It is required for maintaining vascular endothelial cell integrity and survival during murine embryo development and in adult and may be involved in modulating differentiation of hematopoietic cells in adult. Tie-1 exhibits poor tyrosine kinase activity and signals via forming heterodimers with Tie-2,inhibiting Tie-2 signaling mediated by Angs. This inhibition can be relieved by Tie-1 ectodomain cleavage mediated by tumor- and inflammatory-related factors,which causes destabilization of vessels and initiates vessel remodeling. Up-regulated Tie-1 expression has been found not only in some leukemia cells and tumor related endothelial cells but also in cytoplasm of carcinoma cells of a variety of human solid tumors,which is associated with tumor progression. In addition,it has pro-inflammatory functions in endothelial cells and is involved in some inflammatory diseases associated with angiogenesis. Recent research indicated that Tie-1 gene ablation exhibited significant effects on tumor blood- and lymph-angiogenesis and improved anti-Ang therapy,suggesting Tie-1 may be a potential target for tumor anti-angiogenesis treatment.